2021
DOI: 10.46281/ijafr.v6i2.1082
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Balance Sheet for Banks in India Using Goal Programming

Abstract: In earlier years, there was abundance of funds in banks in the form of demand and savings deposits. Hence, the focus of banks was mainly on asset management. But intense competition and volatility of interest rate due to banking reforms reduced the availability of low-cost funds and therefore, banks focused on liability management as well. These pressures call for structured and comprehensive measures and not just ad hoc action. This is how banks started to concentrate more on the management of both sides of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This model considered the most important considerations regarding the institution's finances, the law, and bank policy. An Indian bank's assets and liabilities were optimized through goal programming by Tanwar et al (2021), and the results revealed that goal programming might help optimize and boost profitability. In addition, Garcia et al (2010) proposed several goal programming methods for determining the weights of business performance measures by employing constrained regression.…”
Section: Pakistan Journal Of Statistics and Operation Researchmentioning
confidence: 99%
“…This model considered the most important considerations regarding the institution's finances, the law, and bank policy. An Indian bank's assets and liabilities were optimized through goal programming by Tanwar et al (2021), and the results revealed that goal programming might help optimize and boost profitability. In addition, Garcia et al (2010) proposed several goal programming methods for determining the weights of business performance measures by employing constrained regression.…”
Section: Pakistan Journal Of Statistics and Operation Researchmentioning
confidence: 99%
“…Fiedler et al (2002) described that due to advancement in software, earnings and value could be supported by a single, integrated, and analytical framework to determine earnings sensitivity and future market valuation across dynamically modeled balance sheets. Tanwar et al (2021 used a goal programming model to optimize the asset and liabilities of the banks while compiling the various constraints.…”
Section: Literature Review On Asset Liability Management In Bankingmentioning
confidence: 99%